VEGETATIVE GROWTH AND FRUITING INDUCTION OF LENTINULA EDODES STRAINS ON DIFFERENT SUBSTRATES - SMITA PURI (The Bioscan, 2012)
Lentinula edodes or Shiitake is an edible and medicinal mushroom, widely used for preparation of dietary supplements and other delicacies. Rich diversity of mushrooms is found in Uttarakhand state of India, besides other flora fauna. Two strains of L. edodes fungus were collected from Uttarakhand hills. To study the physiological and yield attribute, mycelial growth and yield of L.edodes isolates werecompared on different media, temperature, pH and agricultural wastes like sugarcane bagasse, paddy straw, poplar sawdust, coirpith, teak and sal sawdust alone and in combinations of 1:1. Potato dextrose agar (PDA) medium was found to be superior in terms of radial growth. The fungus showed maximum radial growth at 25ºC and acidic pH. The cultivation of mycelium was successful at all the substrates tested. On the basis of morphological, cultural and yield characteristics, strain L1 was superior to L2.